ANALISIS KEBERHASILAN AKADEMIK MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS MUHAMMADIYAH METRO - Nego Linuhung; Nurain Suryadinata (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
The quality of a student can be demonstrated from academic success as reflected in the cumulative achievement index (GPA) achieved. This study aims to analyze the factors that influence the academic success of students of the Mathematics Education Study Program at Muhammadiyah Metro University, examine the significance of the overall and individual model parameters, and form a binary logistic model of student success. The subjects of this study were students in Mathematics Education at Muhammadiyah University of Metro. While the sample used is students of the 2-6 semester Mathematics Education of Muhammadiyah Metro University 2017/2018 Academic Year as many as 108 students. Based on the results of the study and discussion, the conclusions are: 1) Based on the variables that have been included in this study, the factors that most influence the academic success of students as indicated by GPA acquisition with the "With Praise" category are the major factors taken students while studying in high school (SMA) / equivalent; 2) The overall model parameters have a significant influence on the academic success of students and individually / partially the most significant influence is the departmental factor; 3) The regression model that is formed isg(x) = -0,924-2,575(Jurusan_1)